The External Aspects of an Object in Husserl’s Phenomenology - Viktor Zavřel (Profil, 2020)
Husserl's phenomenology is widely considered an idealistic philosophy, this article aims to present the empirical side of Husserl's philosophy by analyzing a key epistemological concept, i.e., an object. The research of the first and last of Husserl's writings (which are devoted to the issue of constituting logic) will present a necessary part of the phenomenological conception of the object – its external aspect. This aspect is, on the one hand, based on the general phenomenological conception of knowledge, which prima facie contains the features of idealism, but, on the other hand, by examining the concepts below, the strength of the bond that connects this conception with the outside should be clarified.